Evaluation and Comparison of the Accuracy and Efﬁcacy of Alvarado and Appendicitis Inﬂammatory Response Scoring in Acute Appendicitis - Santosh Mishra; Archan Ghimire; Rajesh Poudel; Sagun Thapa; Sanjay Shrestha; Pradip Chhetri (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Acute appendicitis (AA) is one of the most common causes of acute abdominal pain. Early surgery for acute appendicitis may lead to inadequate evaluation of differential diagnoses of acute abdominal pain and increases the chances of negative appendectomy, whereas delaying it leads to potential complications. Appendicitis inﬂammatory response (AIR) score, has been created to overcome shortcomings of the Alvarado score. In this, a mathematical model focused on detecting perforated appendicitis has been used. Unlike previously reported scores, this included C-reactive protein (CRP), which had been previously reported to have high accuracy in discriminating between simple and advanced acute appendicitis. MATERIAL AND METHODS Observational Cross sectional study was done in all patients admitted to UCMS hospital diagnosed to have acute appendicitis from October 2019 to March 2021. The primary objective was to determine if use of Appendicitis Inﬂammatory Response Score is better suited for planning management of patients with acute appendicitis. Comparison between groups was done with one-way Analysis of Variance (ANOVA). Receiver Operating Curve (ROC) was used to identify whether Appendicitis inﬂam- matory response (AIR) score or Alvarado score was good predictor of acute appendicitis. Sensitivity, Speciﬁcity and Area under Curve (AUC) was used as indicators to predict the acute appendicitis. RESULTS In our study, the sensitivity of Appendicitis inﬂammatory response (AIR) score is high (85.4%) as compared to 82.3% of Alvarado score. CONCLUSION We concluded that Appendicitis inﬂammatory response (AIR) score is more reliable scoring system for the diagnosis of acute appendicitis and its use can be justiﬁed over the pre-existing Alvarado scoring.